2010
DOI: 10.1586/erv.10.1
|View full text |Cite
|
Sign up to set email alerts
|

6th World Congress of the World Society for Pediatric Infectious Diseases (WSPID)

Abstract: The 6th World Congress of the World Society for Pediatric Infectious Diseases (WSPID) was held in Buenos Aires, Argentina between 18 and 22 November, 2009. This is one of the biggest pediatric infectious disease assemblies in the world and it brought together pediatricians and pediatric infectious disease and vaccine experts. Numerous topics about pediatric infectious diseases were discussed during the congress. The scientific program focused on vaccines and vaccine-preventable diseases, including epidemiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
1
Order By: Relevance
“…Statistically significant declines were seen in all-cause pneumonia, pneumococcal pneumonia, and otitis media between the cohorts. The observed significant reduction in pneumococcal disease was non-inferior to that observed with the 3+1 dosing schedule [35][36][37].…”
Section: Effectiveness Of the Reduced-dose Schedule (2+1) In Childrenmentioning
confidence: 58%
See 1 more Smart Citation
“…Statistically significant declines were seen in all-cause pneumonia, pneumococcal pneumonia, and otitis media between the cohorts. The observed significant reduction in pneumococcal disease was non-inferior to that observed with the 3+1 dosing schedule [35][36][37].…”
Section: Effectiveness Of the Reduced-dose Schedule (2+1) In Childrenmentioning
confidence: 58%
“…Patrzałek et al investigated the influence of pneumococcal vaccination on the radiologically confirmed pneumonia admission rates in the hospital [8]. The results compare well with the 3+1 PCV7 dosing schedule [35][36][37].…”
Section: Effectiveness Of the Reduced-dose Schedule (2+1) In Childrenmentioning
confidence: 90%
“…Önemli mortalite ve morbidite nedeni olmasının yanında aşı ile de önlenebilir bir infeksiyon etkeni olması rotavirüsü halk sağlığı açısından önemli bir yere koymaktadır [38] . Ülkemizde ise maliyet, rotavirüs aşısının ulusal aşılama programına dahil edilmesinin önündeki engel olarak göze çarpmaktadır [39] . Adenoviral gastroenteritler için ise herhangi bir aşılama çalışması bulunmamaktadır.…”
Section: Discussionunclassified